1994
DOI: 10.1289/ehp.94102s10185
|View full text |Cite
|
Sign up to set email alerts
|

Oxidants, antioxidants, and respiratory tract lining fluids.

Abstract: Respiratory tract lining fluids (RTLFs) are a heterogeneous group of substances covering the respiratory tract epithelial cells (RTECs) from nasal mucosa to alveoli. Antioxidants contained in the RTLFs can be expected to provide an initial defense against inhaled environmental toxins. The major antioxidants in RTLF include mucin, uric acid, protein (largely albumin), ascorbic acid, and reduced glutathione (GSH). RTLF antioxidants can be augmented by such processes as transudation/exudation of plasma constituen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(76 citation statements)
references
References 84 publications
2
74
0
Order By: Relevance
“…The thiol containing antioxidants glutathione and albumin are found in high concentrations in the ELF27 and are nitrosated by NO redox equivalents (N 2 O 3 and N 2 O 4 ) to produce S-nitrosothiols (RS-NO) 26…”
Section: Discussionmentioning
confidence: 99%
“…The thiol containing antioxidants glutathione and albumin are found in high concentrations in the ELF27 and are nitrosated by NO redox equivalents (N 2 O 3 and N 2 O 4 ) to produce S-nitrosothiols (RS-NO) 26…”
Section: Discussionmentioning
confidence: 99%
“…Numerous human, animal, and vegetation studies have shown that the first line of defense against any oxidative challenge is mobilization of antioxidants (Heath et al, 2009;Samet et al, 2001;Schelegle et al, 2007). For example, O 3 reacts with ascorbic acid, reduced glutathione, and uric acid antioxidants contained in the human epithelial lining fluid (ELF) that scavenge free (Avissar et al, 2000;Ballinger et al, 2005;Cross et al, 1994;Mudway et al, 1996;Samet et al, 2001).…”
Section: Induction Phase Responsementioning
confidence: 99%
“…These findings provide the first evidence that GSA is formed in vivo. The assay was sufficiently sensitive to detect GSA in samples collected by a lavage process that typically gives ∼100-fold dilution of the epithelial lining fluid [42]. Based on this dilution factor, actual GSA concentrations could be several hundred nanomolar.…”
Section: Analysis Of Biological Samplesmentioning
confidence: 99%